Ionic mass transfer in the electrolysis of flowing solutions : The electrodeposition of copper under mass-transfer control on tubular electrodes - Bazán, Julio César (1964)
Ionic mass transfer for the electrodeposition of copper from aqueous copper sulphate-sulphuric acid solutions has been studied on tubular stainless steel electrodes. The following parameters were varied: rate of flow, copper ion concentration, viscosity, height and diameter of tubular electrodes, and temperature. The data can be correlated by the dimensionless equation Sh = 0·647 Re1/2Sc1/3. The temperature coefficient of the kinetic mass-transfer constant is 1.2, corresponding to an experimental heat of activation of 3850 ± 200 cal/mol. The solution of the momentum- and heat-transfer equations worked out by Eckert for flat plates, according to von Kármán's treatment, and recently extended by Wranglén to the analogous masstransfer problem, can be applied under certain conditions to tubular electrodes.